Cryoglobulinemia and hepatitis C virus - N. V. Dunaeva; E. V. Esaulenko (Журнал инфектологии, 2014)
The review presents recent data on cryoglobulinemiaassociated with a hepatitis C virus: prevalence, pathogenesis, clinical manifestations, laboratory diagnostics, approaches to therapy.